Application of continuity of care based o Internet Plus in rehabilitation care of patients undergoing total hip arthroplasty: A review of literature (“互联网+延续性护理”在全髋关节置换术后患者康复护理中的研究进展) - CHENG Mingcui (程明萃); QIAN Bo (钱博); WANG Kaili (王凯丽); KANG Jingjing (康京京); ZHAO Jia (赵佳); LI Tinghui (李婷慧) (中西医结合护理)
At present, the model of Internet Plus continuity of care ensures that patients receive continuous and effective care interventions in the family and community, thereby improving their quality of life and accelerating the recovery process. This paper analyzed and summarized the application of continuity of care based o Internet Plus model in patients after total hip arthroplasty, in order to provide reference for healthcare professionals to provide multifaceted care for patients after surgery. (人工髋关节置换术后患者出院后的居家康复管理是加快术后康复的关键。“互联网+延续性护理”模式可确保患者在家庭和社区中得到持续有效的护理干预, 从而提高其生活质量, 加速康复进程。本文就“互联网+延续性护理”模式在髋关节置换术后患者中的应用进行分析和总结, 旨在为髋关节置换术后患者的康复治疗提供参考。)